Kolaborasi Remaja dan Ibu Rumah Tangga dalam Mengembangkan Pariwisata Sungai Berbasis Konten Kreatif Digital - Suginam, Suginam; Mesran, Mesran; Rosnizam, Rosnizam (Sekolah Tinggi Ilmu Manajemen Sukma Medan, 2026)
This community service program aims to develop the river tourism potential in Kampung Jandi Mulia through collaboration between youth and housewives in creating digital creative content. The activities included digital literacy training, promotional video production, and social media-based marketing strategies. Analysis results showed a significant increase in participants’ knowledge, technical skills, and self-confidence, with an average score improvement of 28–30 percentage points compared to before the training. Participant satisfaction responses were highly positive, with 85% expressing satisfaction to high satisfaction with the program. This initiative also revived tourism promotion after infrastructure damage caused by flash floods and opened opportunities for the local creative economy. However, the program faced limitations in training duration and technical facilities, posing challenges to long-term sustainability. These findings indicate that community-based digital capacity building can be an effective strategy in optimizing local tourism potential.